Walking the Walk: The Case for Internal Equity, Diversity, and Inclusion Work Within the Canadian Public Health Sector - Ankur Shahi; Fareen Karachiwalla; Nagma Grewal (Mary Ann Liebert, 2019)
Equity is fundamental to public health practice. However, limited work has evaluated public health units, as employers, in ensuring equitable workplaces. Public health units must examine their policies for promoting equity, diversity, and inclusiveness. We suggest strategies that these organizations may adopt to establish a diverse workforce, including programs of responsibility, broader advertisement of employment opportunities, and standardized application processes. These practices are site dependent and are more effective when supported by senior management. By considering these strategies, institutions of public health can improve equity, diversity, and inclusion in their workplaces while addressing health equity in the communities they serve.